Psicologia e educação no contexto das secretarias municipais: algumas contribuições para novas práticas - Cunha, Beatriz Belluzzo Brando [UNESP]; Betini, Gilmara (Conselho Federal de Psicologia, 2003)
Visando a refletir sobre diferentes formas de pensar e fazer dos psicólogos que atuam na Educação Municipal, participamos da Comissão de E-ducação do CRP-06/subsede de Assis e entrevistamos psicólogas aí envolvidas. Verificamos que suas ações - condicionadas ao modelo político-ideológico ado-tado pela gestão municipal e pela formação acadêmica recebida - caracterizam-se por práticas tradicionais e/ou compartilhadas por outros profissionais, que não vêm contribuindo para a reversão do quadro de produção do fracasso escolar. Assim, consideramos urgente a revisão dos aspectos relativos à formação dos psicólogos, às práticas atualmente implementadas e ao engajamento dos órgãos dessa classe para a consolidação de uma psicologia mais comprometida com a cidadania.

The paper reports on our reflection upon the different way psychologists think and act in their practice within the Municipal Educational context. As members of the Education Committee of the Regional Board of Psychologists (Branch of Assis), we have conducted interviews of practicing psy-chologists within the education context. We have found that the practitioners' ac-tions are guided either by the political/ideological model of the city administration or by their academic background. These are characterized by traditional ways of practice and/or shared by other professionals. Such practices have not contributed to changes in the current state of school failure. Therefore, we urge the reviewing of certain aspects concerning the psychologist's professional development, the current professional practices and the efforts of professional psychologycal organizations to a consolidation of a professional practice that is committed to citizenship.
Psychology and education in the municipality context: some contributions towards new practices
Keywords: Psicologia escolar; Psicólogos da educação municipal; Formação profissional; Fracasso escolar; Educational psychology; Psychologists of the municipal education; Psychologist's professional development; School failure